The story of the lost child [large type] - Ferrante, Elena (Ferrante, Elena. Amica geniale., 2016)
Here is the dazzling saga of two women, the brilliant, bookish Elena and the fiery uncontainable Lila. In this book, both are adults; life's great discoveries have been made, its vagaries and losses have been suffered. Through it all, the women's friendship, examined in its every detail over the course of four books, remains the gravitational center of their lives. Both women once fought to escape the neighborhood in which they grew up -- a prison of conformity, violence, and inviolable taboos. Elena married, moved to Florence, started a family, and published several well-received books. But now, she has returned to Naples to be with the man she has always loved. Lila, on the other hand, never succeeded in freeing herself from Naples. She has become a successful entrepreneur, but her success draws her into closer proximity with the nepotism, chauvinism, and criminal violence that infect her neighborhood. Yet somehow this proximity to a world she has always rejected only brings her role as unacknowledged leader of that world into relief. For Lila is unstoppable, unmanageable, unforgettable! Against the backdrop of a Naples that is as seductive as it is perilous and a world undergoing epochal change, this story of a lifelong friendship is told with unmatched honesty. Lila and Elena clash, drift apart, reconcile, and clash again, in the process revealing new facets of their friendship.